The system of innovative thinking (Journal of Philosophy Culture and Political Science, 2018)
«The strategy «Kazakhstan-2050 – a new policy established state» Message of the President of the Republic of Kazakhstan – the President Nursultan Nazarbayev to the people of Kazakhstan was fully formulated innovative thinking. This Message is result of many years’ theoretical, practical and personal searches. 14 December in ‘Astana Opera’ the President of Kazakhstan Nursultan Nazarbayev in his introduction, for the first time used the term «innovative thinking». In the Message, the President said: «To be on the crest of new technological wave, to create absolute innovation is not possible for all countries. We have to clearly realize it» and concluded: «We are a young nation, and we will do it». Clarifying the definition of «innovation», the Head of state says that our young people need absolute innovation. Keywords: innovation, the new policy of development, the system of a new thinking, a new generation, patriotism.